Using Dynamic Facade for Indoor Air Quality, Thermal Comfort and Energy Efficient Air Conditioning (University of Khartoum Engineering Journal, 2022)
Buildings present both a major impediment to reducing our reliance on the burning of dwindling reserves of fossil fuel and a real opportunity for achieving significant reduction in global carbon emissions. Dynamic facade, using Dynamic Insulation (DI), is an energy-efficient method of supplying pre-tempered filtered ventilation air to a building through an air-permeable dynamically insulated envelope or facade. One of the important features of DI is that it effectively decouples ventilation rate from energy use. In theory, it should workwell with all buildings, including homes, schools, offices and sports facilities where high occupancy is the norm. This paper investigates the use of DI in a building facade for zone local insulation and ventilation. The savings in energy and CO2 reduction are quantified against existing standards in the Gulf Region. The results show that DI can provide tempered fresh air, raise energy efficiency and reduce air conditioning energy demand without compromising Indoor Air Quality (IAQ) or thermal comfort level.